2020
DOI: 10.1002/jbmr.4304
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination for Coronavirus Disease 2019 (COVID-19) and Relationship to Osteoporosis Care: Current Evidence and Suggested Approaches

Abstract: The development of coronavirus disease 2019 vaccines has proceeded at an unprecedented pace, with numerous trials conducted simultaneously across the world as a result of massive technological and financial resource expenditures. With multiple vaccines having now received regulatory approval, public health efforts to promote widespread vaccine dissemination are currently underway. There has been particular emphasis placed on vaccination of older populations, the age group in which COVID-19 infection has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 55 publications
0
20
0
3
Order By: Relevance
“…Hence, it is recommended their administration be separated from COVID-19 vaccination by a 1-week interval. An interval of 4–7 days is also recommended between the administration of denosumab and romosozumab and COVID-19 vaccination, due to potential injection site reactions, such as localized pain, swelling, and/or erythema [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is recommended their administration be separated from COVID-19 vaccination by a 1-week interval. An interval of 4–7 days is also recommended between the administration of denosumab and romosozumab and COVID-19 vaccination, due to potential injection site reactions, such as localized pain, swelling, and/or erythema [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tsourdi and colleagues addressed this question, and could show that osteoporosis is not associated with a higher risk of COVID-19 infection. Further, it was shown that osteoporosis treatments do not interfere with the efficacy of any COVID-19 vaccination, but possible long-term side effects, although not very likely, such as cross-reactivity of the drugs, have not been evaluated yet [281]. Since the importance of physical activity and exercise to prevent fractures in osteoporotic patients was previously established, it is also important to address the question of how osteoporosis patients might be endangered due to quarantine, staying at home, and movement restrictions [282].…”
Section: Future Perspectives Of Anabolic and Catabolic Treatments For...mentioning
confidence: 99%
“…For intravenous bisphosphonates, while there is no evidence to suggest the concurrent administration of vaccine and bisphosphonates alters each other’s efficacy, it is empirically recommended to have 4 to 7 days interval between bisphosphonates and vaccine due to the possibility of acute-phase reaction. [ 62 ] Also, if patients who received intravenous bisphosphonates have fever or myalgia over 3 days, evaluation for COVID-19 infection should be considered since the acute phase reaction of bisphosphonates rarely extends over 3 days. [ 63 ] Oral bisphosphonates do not need to be discontinued during vaccination.…”
Section: Strategies In Vaccinationmentioning
confidence: 99%
“…[ 64 ] However, since denosumab can cause injection site dermatitis or eczema,[ 65 ] injections are recommended to be administered at contralateral arms or different sites, or with 4 to 7 days of interval. [ 62 ] Teriparatide and abaloparatide may also induce local injection site reactions but usually do not cause confusion because the injection sites are different from those of vaccines. [ 66 ] Therefore, teriparatide and abaloparatide can be continued during vaccination.…”
Section: Strategies In Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation